2012
DOI: 10.1158/1055-9965.epi-12-0327
|View full text |Cite
|
Sign up to set email alerts
|

Time to Get Serious About Skin Cancer Prevention

Abstract: In this commentary, we discuss the skin cancer epidemic in the United States and provide data to indicate that the United States public is not protecting itself from ultraviolet radiation, the primary risk factor for melanoma, and nonmelanoma skin cancer. In our opinion, skin cancer control in this country may be hindered by uncertainty about the effectiveness of sun protection strategies, inconsistent messages about the relative effectiveness of sun protection measures by federal and national organizations, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 91 publications
0
43
0
1
Order By: Relevance
“…There is also a skin cancer epidemic in the United States [37]. We agree with Lazovich that it is time to get serious about better protecting ourselves and our children from the risk of future skin cancer [37]. Further targeted public sun safety campaigns are warranted.…”
Section: Recommendationsmentioning
confidence: 85%
See 1 more Smart Citation
“…There is also a skin cancer epidemic in the United States [37]. We agree with Lazovich that it is time to get serious about better protecting ourselves and our children from the risk of future skin cancer [37]. Further targeted public sun safety campaigns are warranted.…”
Section: Recommendationsmentioning
confidence: 85%
“…Incidence rates of cutaneous melanoma have been increasing during the last 30-40 years; the highest rates have been documented in Australia and New Zealand (27.9/100,000 among males and 25.0 among females) and in North America (10.9/100,000 among males and 7.7 among females) [36]. There is also a skin cancer epidemic in the United States [37]. We agree with Lazovich that it is time to get serious about better protecting ourselves and our children from the risk of future skin cancer [37].…”
Section: Recommendationsmentioning
confidence: 99%
“…The optimal approach is likely to be a comprehensive one 26) , that addresses personal factors as part of a broader program promoting the development of workplace contexts that positively support sun protection 43) . Although we found that the Pro-Tan Attitude Score was negatively associated with protective practices, indicating that attitudes merit attention, this study both confirms and extends our earlier findings about the relatively strong association of workplace equipment provision and supportive culture with workers' sun protection 24,41) , confirming that employer-led interventions may offer a potentially promising direction for policy development and implementation 25) .…”
Section: Discussionmentioning
confidence: 99%
“…Secondary prevention is based on early detection of skin cancer. Early detection involves regular skin examinations for high-risk individuals and screening programs to identify those at high risk (WHO, 2003;Geller et al, 2005;Jones et al, 2007;Lazovich et al, 2012).…”
Section: What Turkish Nurses Know and Do About Skin Cancer And Sun Prmentioning
confidence: 99%